Karakteristik Bioplastik Dari Komposit Limbah Cair Tahu (WHEY) Dan Serat Daun Nanas (Ananas Comosus) Dengan Hidrokoloid Carboxymethyl Cellulose (CMC) - Inka Novela; Idral Amri; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bioplastics have different characteristics according to their raw materials. One of the raw materials that has the potential to be made into bioplastics is whey and pineapple fiber because it has high starch and cellulose content besides that it is easy to degrade. The general aim of this research are to study the impact of whey, pineapple leaf fiber and carboxymethyl cellulose in mechanical properties and morphology of bioplastic. The castingmethod in this research consist of whey, pineapple leaf fiber, and carboxymethyl cellulose with composisition of whey (10-50% v / v), composition of pineapple leaf fiber (1-3 gr), andcomposition of carboxymethyl cellulose (2.5-4.5% b / v). The analysis of bioplastic characterization are biodegradability, tensile strength, elongation, modulus young, tearstrength, Scanning Electron Microscopy (SEM) and hydrophobicity. The most react variable is the composition of pineapple leaf fiber followed by carboxymethyl cellulose and whey. Thebest process condition is found on bioplastic with composisition whey 30% v/v, pineapple leaf fiber 1 gr and carboxymethyl cellulose 3.5% b/v with the value is biodegradation time for 23days, tensile strength 15.85 MPa, elongation 18.24%, modulus young 86.9 MPa, tear strength strength 690.63 gf/mm and hydrophobicity 6.818%. Micrograf analysis shows thatfiller distribution is not equally on whey matrices and still has a clod.Keywords: bioplastic, cellulose, pineapple leaf fiber, whey